(untitled) (Rehabilitation and Recreation, 2024)
The use of electromechanical and robotic devices in neurorehabilitation can significantly improve the quality of life and daily activities of patients who have suffered a stroke or suffer from other movement disorders. The purpose of this scientific work is to study and analyze the integration of innovative methods into rehabilitation programs for patients after a stroke, and the creation of new rehabilitation algorithms for the restoration of cognitive functions in the early stages of rehabilitation. Material. The clinical study was conducted in the period from 2022 to 2024 based on the Neurological Department of the Municipal Enterprise “Poltava Regional Clinical Hospital named after M.V. Sklifosovsky of Poltava Regional Council”. A total of 103 people took part in the study, of which 44 were women (42.72%) and 59 were men (57.28%). The age of the total group ranged from 45 to 64 years, with an average age of Criteria for assignment to subgroups 1.1–1.4: age from 45 to 74 years, both men and women with ischemic stroke, first (and only) stroke in history, with moderate cognitive impairment, mild dementia, without severe aphasia, epilepsy or epileptic syndromes in the anamnesis and available informed consent to participate in the study. Results. During stroke recovery, the use of a computer stimulation program can successfully improve cognitive function in 54.0% of patients. This is significantly different from the typical standard rehabilitation recovery (22.5%). Conclusions. The use of innovative methods in rehabilitation programs after a stroke helps to improve the results of the recovery of motor functions and increase the quality of life of patients. For the successful implementation of innovative methods, it is necessary to ensure appropriate training of personnel, create appropriate conditions, and carry out individualization of rehabilitation programs. Research on the longterm effects of innovative methods and their impact on the quality of life of patients is necessary to provide an objective assessment of their effectiveness.